SELECTED FEATURES OF CIVIL LAW AND CIVIL PROCEDURE IN POLISH-ENGLISH TRANSLATION - ZEDLER, Feliks (Comparative Legilinguistics, 2010)
The articles touches upon selected problems connected with polysemous words occurring Polish language of civil law and civil procedure. The author presents the meanings of two terms that is: kurator and dowód. Especially kurator is a very troublesome term under Polish law as it has about seventeen meanings depending on the context in which this term is used. Next, he presents translative equivalents of those words which may be found in selected bilingual Polish-English dictionaries of legal terms. Finally, it is concluded that bilingual dictionaries rarely help to solve the problem of polysemy as there are no contextual indexes which would help choose the proper English equivalent. What is more, some suggested dictionary equivalents are questionable.